Literature Study: Effectiveness of Using Interactive Media "Google Earth" in Social Studies Learning for Elementary School Students - Rut Rima Ria; Gati Sry Handayani (International Journal of Educatio Elementaria and Psychologia, 2024)
This study aims to evaluate the effectiveness of using interactive media “Google Earth” in learning Social Studies in elementary schools. As a technology-based learning tool, Google Earth allows students to explore geographical representations of the world visually and interactively, thus enhancing their understanding of spatial and geographical concepts. The results show that the use of Google Earth can significantly increase student engagement, facilitate visual exploration and encourage discovery learning. In addition, it helps students connect theoretical concepts with real contexts through engaging visual simulations. This study recommends the integration of Google Earth into the social studies curriculum as an innovative learning medium. With proper management, Google Earth has the potential to support more interactive and meaningful learning for elementary school students. Further research is needed to explore its impact in a broader and more diverse context.